El confinamiento social y el carácter en los estudiantes de la carrera de Psicopedagogía de la Universidad Nacional de Chimborazo - Andrade Manzano, César Augusto (2023)
The present research work conducts a specific study of the character traits of sixth, seventh and eighth semester students of the Psychopedagogy program at the National University of Chimborazo and evaluates the behavioral changes that are manifested after the COVID-19 pandemic, the importance of this research is to demonstrate the behavioral changes that become evident after living in confinement. This research has been proposed in order to clarify how character, being an important component of personality, enables self-regulation and its interpersonal and social management, for which the research is conducted from a quantitative approach, without the possibility of manipulating the research under-study variables, which implies that the phenomena are presented as they are manifested in their natural context. subsequently, the predominant character traits in the groups of students investigated are described in order to obtain patterns that allow us to understand the personality traits and their manifestations, which will help us to understand human behavior in some way. Among the main research results we consider sharing with our readers the changes experienced by the investigated students during the state of alarm for the COVID-19 pandemic, for which it was crucial to investigate and know its context and necessarily seek and use the technical complement that allows us to visualize the character traits in a scientific way, these contributions have led us to understand that this research process did not strive to find defects or flaws in the will or behavior but, rather, how the confinement phenomenon could alter in a diverse and natural way the manifestations of behavior before the actions of daily life. Investigated people demonstrate states of anxiety and fear of people when resuming daily activities, thus altering the social dynamics, The present study provides detail evidence of every concern, psychological discomfort is also evident, which in some way is reflected in an increase in situations of instability, impulsive or out-of-control reactions, states of depression and inability to resume daily activities normally, in addition it has been noted that sleep disturbances are also evident in the population. The usefulness of the present study recommends good communication practices on active behavior patterns, interpersonal and social practices. in an effort to promote student leaders with dynamic behaviors, emotional balance, good habits, and excellent interpersonal and social practices.